Influence of allopurinol on thiopurine associated toxicity: A retrospective population‐based cohort study. Issue 5 (20th November 2020) - Houwen, Jeroen P.A.; Egberts, Antoine C.G.; de Boer, Anthonius; van Maarseveen, Erik M.; Houwen, Roderick H.J.; Lalmohamed, Arief
Abstract : Aims: Thiopurines are important for treating inflammatory bowel disease, but are often discontinued due to adverse effects. Concomitant use of allopurinol might lower the risk of these unwanted effects, but large studies in the general population are lacking. The aims of this study were to evaluate rates of hepatotoxicity, myelotoxicity, pancreas toxicity and therapy persistence in adult thiopurine users with or without allopurinol. Methods: A retrospective population‐based cohort study was conducted within current thiopurine users (Clinical Practice Research Datalink). Among these patients, co‐use of allopurinol was compared to non‐use. Hazard ratios (HRs) for hepatotoxicity, myelotoxicity and pancreatitis were derived using time‐dependent Cox proportional hazards models, and were adjusted for potential confounders. Persistence of thiopurine use was evaluated using Log‐rank statistics. Results: Patients using thiopurines ( n = 37 360) were identified of which 1077 were concomitantly taking allopurinol. A 58% decreased risk of hepatotoxicity was observed in those concomitantly taking allopurinol (HR 0.42; 95% CI 0.30–0.60; NNT 46). Rate of myelotoxicity (HR 0.96; 95% CI 0.89–1.03) was not influenced. Risk of pancreatitis was increased (HR 3.00; 95% CI 1.01–8.93; NNH 337), but was only seen in those with active gout (suggesting confounding by indication). Finally, allopurinol co‐users were able to maintain thiopurine therapy over twice as long as those not on allopurinol (3.9 years vs . 1.8 years, P < 0.0001). Conclusion: In thiopurine users, allopurinol is associated with a 58% reduced risk of hepatotoxicity. In addition, thiopurine persistence was prolonged by 2.1 years in allopurinol users. These data support the use of allopurinol in individuals requiring thiopurine therapy.